2021
DOI: 10.21203/rs.3.rs-596463/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infectivity and antigenicity of SARS-CoV-2 B.1.617 variants

Abstract: SARS-CoV-2 has caused the COVID-19 pandemic. Recently, B.1.617 variants have been transmitted rapidly in India. The transmissibility, pathogenicity, and neutralization characteristics of these variants have received considerable interest. In this study, 22 pseudotyped viruses were constructed for B.1.617 variants and their corresponding single amino acid mutations. B.1.617 variants did not exhibit significant enhanced infectivity in human cells, but mutations T478K and E484Q in the receptor binding domain led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Using the double-split reporting system, Wang found that the fusion tendency of the B.1.617 mutant strain was twice that of the D614G reference strain. The increase in furan activity and cell proliferation may account for the increased transmission rate of this lineage [ 60 ].…”
Section: Characteristics Of Vumsmentioning
confidence: 99%
“…Using the double-split reporting system, Wang found that the fusion tendency of the B.1.617 mutant strain was twice that of the D614G reference strain. The increase in furan activity and cell proliferation may account for the increased transmission rate of this lineage [ 60 ].…”
Section: Characteristics Of Vumsmentioning
confidence: 99%